2004
DOI: 10.1002/jbm.b.30094
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo study of hydrogels based on physiologically clotted fibrin–gelatin composites as wound‐dressing materials

Abstract: In this study we have reported the efficacy of three biomaterials: (a) physiologically clotted fibrin-gelatin composite (PFG), (b) PFG graft copolymerized with 2-hydroxyethyl methacrylate (PFG-HEMA), and (c) PFG graft copolymerized with 2-hydroxypropyl methacrylate (PFG-HPMA) as temporary wound-dressing materials using the rat as an animal model. Full-thickness excision wounds were made on the back of female rats weighing about 150 +/- 10 g. The dressings were applied on the wounds and changed periodically at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Collagen forma- tion and maturation at the wound site play an important role in increasing the tensile strength of the healed skin tissue. Remodeling of collagen takes place during the maturation phase, where the molecules are cross-linked to form fibers due to the formation of inter and intra-molecular cross links, thereby increasing tensile strength [33].…”
Section: Tensile Strength Of the Healed Woundmentioning
confidence: 99%
“…Collagen forma- tion and maturation at the wound site play an important role in increasing the tensile strength of the healed skin tissue. Remodeling of collagen takes place during the maturation phase, where the molecules are cross-linked to form fibers due to the formation of inter and intra-molecular cross links, thereby increasing tensile strength [33].…”
Section: Tensile Strength Of the Healed Woundmentioning
confidence: 99%
“…In one study, Fbn-gelatin composite film was shown to exhibit a high equilibrium content of water, which could effectively improve the efficacy and properties of the matrix when applied as a wound dressing. 82 In other studies, a physiologically coated Fbn-chitosan gelatin composite film was shown to provide a fibrous and porous structure with a high water absorption capacity, which could improve the encapsulation efficacy of hydrophilic protein and peptides. 83 Hepatic cell-seeded Fbggelatin matrix stabilized by thrombin exhibited a very high compressive strength.…”
Section: Fbg and Fbn Tubes As Vascular Graftmentioning
confidence: 98%
“…Photographs of the wound healing patterns were taken for qualitative analysis [28] 2.3.3. Weight measurement Weight of mice were recorded before the surgery with an electronic mass balance (accurate to 0.01 g) and again at time of sacrifice.…”
Section: Wound Closure Measurementmentioning
confidence: 99%